Total Oxidation of Isopropanol in Its Liquid Phase, at a Low Temperature in the Presence of Prepared and Characterized Zinc Oxide - Younes Dehmani; Abdellatif Amhoud; Sadik Abouarnadasse (International Journal of Analytical Chemistry)
The complete oxidation of isopropanol in its liquid phase at a low temperature was studied in the presence of zinc oxide (ZnO). This solid was prepared with the precipitation method. Structural analysis (infrared in Fourier transform and diffraction of X-rays) and textured (adsorption/desorption of N2) were conducted for the wurtzite structure results, an IV type isotherm with a type H3 hysteresis. This solid presents a good catalytic activity against the complete oxidation of isopropanol, a constant of selectivity equal to 1; however, the studied temperatures were 40, 60, and 80°C. In addition, a kinetic study of the oxidation was performed and showed that the reaction follows a successive mechanism isopropanol-acetone-carbon dioxide. The low value of the apparent energy of the activation of this solid confirms the high value of the initial rate of the catalytic oxidation reaction of isopropanol in the temperature range studied.